A Strategic Framework for Community Engagement in Oceans and Human Health. Issue 1 (4th May 2022) - Carson, Margaret A.; Doberneck, Diane M.; Hart, Zac; Kelsey, Heath; Pierce, Jennifer Y.; Porter, Dwayne E.; Richlen, Mindy L.; Schandera, Louisa; Triezenberg, Heather A.
Abstract: Over the past two decades, scientific research on the connections between the health and resilience of marine ecosystems and human health, well‐being, and community prosperity has expanded and evolved into a distinct "metadiscipline" known as Oceans and Human Health (OHH), recognized by the scientific community as well as policy makers. OHH goals are diverse and seek to improve public health outcomes, promote sustainable use of aquatic systems and resources, and strengthen community resilience. OHH research has historically included some level of community outreach and partner involvement; however, the increasing disruption of aquatic environments and urgency of public health impacts calls for a more systematic approach to effectively identify and engage with community partners to achieve project goals and outcomes. Herein, we present a strategic framework developed collaboratively by community engagement personnel from the four recently established U.S. Centers for Oceans and Human Health (COHH). This framework supports researchers in defining levels of community engagement and in aligning partners, purpose, activities, and approaches intentionally in their community engagement efforts. Specifically, we describe: (a) a framework for a range of outreach and engagement approaches; (b) the need for identifying partners, purpose, activities, and approaches; and (c) the importance of making intentional alignment among them. Misalignment across these dimensions may lead to wasting time or resources, eroding public trust, or failing to achieve intended outcomes. We illustrate the framework with examples from current COHH case studies and conclude with future directions for strategic community engagement in OHH and other environmental health contexts. Plain Language Summary: Over the past two decades, scientific research on the connections between ocean health and the well‐being and prosperity of people has developed into a distinct field of study known as Oceans and Human Health (OHH). OHH goals seek to improve the health of people; promote the continued use of the world's oceans, lakes, and rivers; and strengthen the ability of communities to respond to public health concerns. OHH research has historically included some level of community outreach and involvement; however, the increasing deterioration of aquatic environments and urgency of public health impacts call for a more organized and deliberate approach to effectively work with community partners. Here, we outline a strategy developed collaboratively by community engagement personnel from the four recently established U.S. Centers for Oceans and Human Health (COHH). This strategy supports researchers in defining approaches to community engagement and in coordinating partners, purpose, activities, and approaches intentionally in their work with communities. We provide examples from current COHH case studies that show how to implement the strategy and describe future directions for community engagement in OHH and other research areas that focus on the interrelationships between people and their environment. Key Points: Effective engagement with communities is paramount to achieving goals and outcomes of Oceans and Human Health research Presented herein is a strategic framework to purposefully align partners, purpose, activities, and approaches for outreach and engagement Adopting a systematic approach to community engagement can help to improve the extent and quality of meaningful partner participation